Is infection associated with pancreatic cancer? A systematic review and meta-analysis of observational studies - Ben-Gang Zhou; Yu-Zhou Mei; Jing-Shu Wang; Jian-Lei Xia; Xin Jiang; Sheng-Yong Ju; Yan-Bing Ding (SAGE Publishing, 2023)
Background and Objectives: Recent observational studies have investigated the association between Helicobacter pylori ( H. pylori ) infection and pancreatic cancer with conflicting data. Therefore, we conducted a systematic review and meta-analysis to assess the potential association. Design: This is a systematic review and meta-analysis. Methods: We searched three databases (PubMed, Embase, and Web of Science) from inception to 30 August 2022. The summary results as odds ratio (OR) or hazard ratio (HR) with 95% confidence interval (CI) were pooled by generic inverse variance method based on random-effects model. Results: A total of 20 observational studies involving 67,718 participants were included in the meta-analysis. Meta-analysis of data from 12 case-control studies and 5 nested case-control studies showed that there was no significant association between H. pylori infection and the risk of pancreatic cancer (OR = 1.20, 95% CI = 0.95-1.51, p  = 0.13). Similarly, we also did not find significant association between cytotoxin-associated gene A (CagA) positive strains, CagA negative strains, vacuolating cytotoxin gene A (VacA) positive strains H. pylori infection, and the risk of pancreatic cancer. Meta-analysis of data from three cohort studies showed that H. pylori infection was not significantly associated with an increased risk of incident pancreatic cancer (HR = 1.26, 95% CI = 0.65-2.42, p  = 0.50). Conclusion: We found insufficient evidence to support the proposed association between H. pylori infection and increased risk of pancreatic cancer. To better understand any association, future evidence from large, well-designed, high-quality prospective cohort studies that accounts for diverse ethnic populations, certain H. pylori strains, and confounding factors would be useful to settle this controversy.